식이유도 비만 마우스에서 대마 추출물의 체중 감량 효과에 대한 예비 연구 - 장유진(Yoo Jin Jang), 임신원(Shinn-Won Lim), 우숙영(Sook-Young Woo), 김수연(Su Yeon Kim), 김도관(Doh Kwan Kim) (Singyŏng chŏngsin ŭihak, 2020)
Objectives This study aimed to investigate the pharmacological effect of cannabis extract on weight loss in diet-induced obese mice. Methods A total of 12 C57BL/6 male mice (Orient Bio), aged 6 weeks, were fed a high-fat diet for 13 weeks to construct a diet-induced obesity model. During the following 5 weeks, diet-induced obese mice were daily administered cannabis extract or sesame seed oil orally along with the high-fat diet. The body weight of each subject was measured weekly. Venous blood was drawn for biochemistry, enzyme-linked immunoassay, and oral glucose tolerance test before and after treatment. Body fat was measured by dual-energy X-ray absorptiometry, and the mesenteric adipose tissue was also measured after sacrifice. We used exact Wilcoxon’s two-sample analyses and generalized estimating equations to test the differences between the cannabis-treated group and control. Results There was significant weight loss (p=0.009) observed in the cannabis-treated mice compared to the control group after 5 weeks of treatment. High-fat diet-induced glucose intolerance in the cannabis-treated group was significantly ameliorated (p=0.032), whereas there were no profound differences between the two groups in terms of other physiological markers, including corticosterone level. Conclusion This study shows that orally administered cannabis extract had a pharmacological effect of weight loss in diet-induced obese mice. This weight loss might be attributed to an increase in energy expenditure and regulation of glucose homeostasis. KCI Citation Count: 1